Demographic and Clinical Characteristics of Adult Measles Patients Attending a Tertiary Care Hospital in Bangladesh - Prabir Mohan Basak; Sabera Gulnahar; Haimanti Shukla Das; Masuda Khan Eusufzi; Atike Mahmud (TAJ: Journal of Teachers Association, 2026)
Background: Measles remains a leading vaccine-preventable cause of morbidity, and epidemiological drift toward older age groups has increasingly placed adolescents and adults at risk of severe disease in settings with incomplete immunisation coverage. Objective: This study characterises the demographic profile, clinical presentation, laboratory findings, complications and in-hospital outcomes of adult measles patients (18–65 years) managed at a Bangladeshi tertiary centre. Methods: A hospital-based cross-sectional study enrolled 108 clinically diagnosed measles patients aged 18–65 years, admitted to the Department of Medicine, Rajshahi Medical College Hospital, between March and July 2026. Demographic, clinical, virological and biochemical variables were recorded prospectively. Data were analysed in SPSS v26.0 using descriptive statistics, the chi-square test and independent-samples t-tests, with p < 0.05 considered significant. Results: The mean age was 22.2 ± 12.6 years (range 1–45); patients were distributed across the 18–30 (42, 38.9%), 31–45 (35, 32.4%), 46–55 (20, 18.5%) and 56–65 (11, 10.2%) year bands, and 60 (55.6%) were female. Only 29 (26.9%) were fully vaccinated, whereas 35 (32.4%) were unvaccinated. Measles-specific IgM was positive in 51 patients (47.2%). The mean peak temperature was 39.6 ± 0.8 °C and mean C-reactive protein 57.2 ± 34.0 mg/L. Pneumonia occurred in 50 patients (46.3%) and 2 (1.9%) required intensive care. Overall, 97 patients (89.8%) recovered, 9 (8.3%) were referred and 2 (1.9%) died. Conclusion: A predominance of incompletely immunised adult patients with a notable complication burden underscores persistent immunity gaps and the need for catch-up vaccination and strengthened surveillance, even though intensive-care requirement and case-fatality in this cohort were low.